Aripirazole-Long Acting Injectable in Pregnant Women with Schizophrenia: A Case Series. (1st June 2022) - Fernández-Abascal, B.; Recio-Barbero, M.; Saenz-Herrero, M.; Segarra, R.
Abstract : Introduction: Long-acting injectable antipsychotics (LAIs) have emerged as a new therapeutic option to treat patients suffering a psychotic disorder. To date, there is a lack of studies regarding safety and clinical use pattern of LAIs in pregnant women. Objectives: Provide evidence and real world clinical data of pregnant women with schizophrenia who have been treated with long-acting aripiprazole monohydrate (aripiprazole once monthly [AOM] condition) during their pregnancy. Methods: Descriptive real-world clinical experiences of pregnant women in treatment with AOM. The information was obtained by reviewing electronic medical records and by direct clinical observation management. Results: The first six case-series describing the pregnancy course of women with schizophrenia treated with AOM. All of them remained psychopathologically stable through pregnancy, and their infants became healthy with normal developmental milestones (Table 1). Conclusions: The favorable results in this case-series suggest that despite the lack of evidence on reproductive safety and treatment with AOM during pregnancy, this therapeutic option should be considered in pregnant women with schizophrenia. However, further research on the use of long-acting antipsychotics in pregnant women is needed. Disclosure: No significant relationships.